Concept of Kushta (calx) and studies carried out on Kushta in unani medicine - Haqeeq Ahmad; Abdul Wadud; Ghulamuddin Sofi; Nasreen Jahan; Hamiduddin (Ancient Science of Life, 2018)
Objective: Kushta (calx) is a well-known dosage form of Unani medicine but has always been condemned by scientific fraternity and even some traditionalists because of certain issues associated with Kushta such as safety, lack of scientific data, adverse effects, and complicated method of preparation. Very few studies are carried out on Kushta in Unani medicine and no study has explored its mechanism of action on scientific basis that may be acceptable widely. Methodology: In this study, the review was done regarding the concept of Kushta in Unani medicine, and studies carried out so far along with a possible explanation of the effectiveness, classical method of preparation, superiority of Kushta over other dosage forms, challenges with use of Kushta, idea of use of herbs in making Kushta, and other issues. Literature on Kushta was collected from classical Unani books and papers published in various journals and analyzed. We found that very few scientific studies have been carried out on Kushta in Unani medicine and that too on certain set topics. Most studies are on physicochemical standardization of Kushta. Conclusion: Study revealed that the research carried out so far is not satisfactory. They are also of preliminary nature. Advance toxicological and pharmacological studies are required to generate strong evidences for wide acceptability, safety, and efficacy of Kushta.